MERANCANG PENDIDIKAN EKONOMI DAN BISNIS ISLAM DI DESA GUNUNG SARI, KECAMATAN PAMIJAHAN, KABUPATEN BOGOR - Tubagus Rifqy Thantawi; Miftakhul Anwar; Ridhatillah Rosamalinda Nasution (Jurnal Pengabdian Kepada Masyarakat Perbankan Syariah: Program Studi Perbankan Syariah., 2023)
Humans as human social beings cannot be separated from the relationship to interact with each other because humans have the obligation as caliphs in the world in creating benefit. One way to realize these benefits is through business activities. Business ethics in Islam demands good behavior, because currently there is a lot of moral damage that is increasingly widespread in companies. The strong empowerment of superior ethics reflects the good name of the company. (Naranjo, 2014). Currently, many business people are only concerned with the goal to get profit by justifying many ways (Muhammad Saifullah, 2011) and they often ignore business ethics and social responsibility. In Islam, Muslims have recognized the Prophet Muhammad as a successful business actor. His success cannot be separated from his example and wisdom as a true business actor. So that in its implementation it is aligned to produce benefits, then we are obliged to implement the values ​​of business ethics (Hamzah et al., 2017). In an effort to obtain halal sustenance, it is an obligation. This will have an impact on social life (Antonio, 2018). Until now, economic development is inseparable from Islamic history. Economics is an inseparable part of human activities. (syahrizal, 2018). In any business, it must always be accompanied by divine values ​​and whatever is done must originate from a spring of life or commonly referred to as maqashid sharia.